Dezercje wojskowych i ucieczki pracowników aparatu bezpieczeństwa ze Związku Sowieckiego w latach 1922–1940 - Kasprzycki, Remigiusz (1972– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
Between 1922 and 1940, from 220,000 to 250,000 soldiers deserted from the Red Army. For the most part, the escapees stayed within the territory of the Soviet Union. However, a numer of the officers and common soldiers deserted abroad. The reasons for the soldiers’ escapes to Poland or Romania were violence, fear, as wel as the forced collectivisation of villages and the religious persecution that took place in the USSR.
p. 75-104
Summary in English.
Keywords: Soviet Union; desertions; Red Army; soldiers; Soviet Union. Raboče-Krestʹânskaâ Krasnaâ Armiâ; deserters - Soviet Union - 1900-1945